معالم التحرك الاستراتيجي لتنويع الصادرات خارج قطاع النفط بالجزائر - bensaha, Mostafa; Bouteldja, Nacer (Finance and Business Economies Review, 2018)
This study seeks to deal with the parameters of strategic movement to the Algerian state in the field of exports diversification outside the oil sector.With having the description and the analyse of the following problem: In what do the images of strategic movement of the Algerian state in its way for diversification of its exports out side the oil sector? Focusing precisely on oil made the Algerian economy faces a lot of repeated shocks. The Algerian government has adopted a range of systematic policies in order to give valuable incentives for the non-oil exports at the following levels: commercial, financial, customs, tax, in addition, to the establishment of some institutions to set up the process of exports diversification such as the Ministry of Commerce, algex , safex.